The refoundation of the University of Guadalajara in 1925. The mystique of the revolution inhibits its autonomy (2018)
Don José Guadalupe Zuno, Governor of the State of Jalisco since 1923, gave higher education its university character again, because since the closing of the old nineteenth-century university and the Institute of State Sciences in 1865, the higher schools directly depended of the State. The foundation of the University of Guadalajara in 1925 was a great event for the country, especially for the northwestern region. This was the second university founded and although the philosophy that founded its existence was based on claiming its secular, popular, scientific character and away from any religious influence, it did not contain in its name nor in its regulations nor its operation the title of Autonomous , despite the fact that the influence of the struggle and conquest of Cordovan autonomy in 1918 was known throughout the continent and spread throughout the world - to the extent that a few years later, in 1829, the University of Mexico also conquered it. In fact, at the University of Guadalajara, this important autonomist antecedent was not taken into account. The influence of the Mexican Revolution, whose armed period had just ended (1910-1917), kept as one of its main claims to promote education and popular culture to the people. In this context, Zuno materialized that great popular aspiration founding the university within that revolutionary paradigm, but he did it from a unipersonal perspective, where the government of the State and the rector were the ones who assumed the university direction, establishing in this way, a directivist model - since the directors took over the University Council, and additionaly they did not recognize the student representations, the democratic election of professors and they subjected the university to the regime, that is to say to the government in turn. The pretext was to link the model with the needs and claims of a society that sacrificed itself for the revolution, but that was assumed as a state battering ram.